Kehamilan Tidak Diinginkan Remaja, Potret Pergaulan Pelajar di Kota Bandung - Sipin Putra (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2021)
This article describes about unwanted pregnancies student Bandung, West Java. This study describes the dating behavior of adolescents that causes unwanted pregnancies. Unwanted pregnancy in adolescents is a phenomenon that occurs in the life student. This condition illustrates that many teenager do not want births as a result of unwanted pregnancies. Free sex of teenagers (students) as usual at Bandung. The social environment and lack of knowledge about reproductive health are the causes of many teenagers going the wrong way in dating. Pregnancy is unwanted as a result of dating that violates religious norms. The assumption that teenagers have to dating eventually leads to sexual activity which is a must in dating. The trend of dating is carried out by student at the junior high school. The trend of dating has resulted in many student undergoing promiscuity for existence and being accepted in their social life. Existence is important for student so that friendship with peers is maintained. The unwanted pregnancy of this student was the result of coercion of promiscuity in dating. Student are not ready to become mothers and hampered to having a brighter future.